Interactive Classroom Training Based on Deep Learning for Mathematics Teachers at Muhammadiyah Vocational Schools in Kendal (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to strengthen the initial readiness of mathematics teachers in the Mathematics Teacher Association of Muhammadiyah Vocational Schools in Kendal Regency to design interactive classrooms based on a pedagogical deep learning approach. The program responded to teachers’ need for pedagogically grounded digital integration, vocational contextual problems, formative assessment, and collaborative lesson design. The activity was conducted on 8 to 9 August 2025 at SMK Muhammadiyah 3 Weleri, Kendal, Central Java, involving 15 mathematics teachers. A product-based participatory capacity-building model, the 4R Workshop, was implemented through reorientation, design, peer review, simulation, and reflective follow-up. Data were collected using pre-test and post-test instruments, product review rubrics, observations, documentation, presentations, and written reflections. The results showed an increase in teachers’ average competence score from 52.00 to 81.75, with an average improvement of 57.45% and a normalized gain of 0.62 in the medium category. Participants produced vocational mathematics learning designs containing objectives, driving questions, contextual problems, collaborative activities, digital media, formative assessment, and reflection. These findings indicate that practice-based, product-oriented, and teacher association-supported training can improve teachers’ initial readiness to design interactive vocational mathematics learning. However, it has not yet measured changes in long-term classroom practice or student learning outcomes.